Accurate prediction of histological grading of intraductal papillary mucinous neoplasia using deep learning - Schulz, Dominik; Heilmaier, Markus; Phillip, Veit; Treiber, Matthias; Mayr, Ulrich; Lahmer, Tobias; Mueller, Julius; Demir, Ihsan Ekin; Friess, Helmut; Reichert, Maximilian; Schmid, Roland M.; Abdelhafez, Mohamed (Endoscopy, 2023)
Background Risk stratification and recommendation for surgery for intraductal papillary mucinous neoplasm (IPMN) are currently based on consensus guidelines. Risk stratification from presurgery histology is only potentially decisive owing to the low sensitivity of fine-needle aspiration. In this study, we developed and validated a deep learning-based method to distinguish between IPMN with low grade dysplasia and IPMN with high grade dysplasia/invasive carcinoma using endoscopic ultrasound (EUS) images.Methods For model training, we acquired a total of 3355 EUS images from 43 patients who underwent pancreatectomy from March 2015 to August 2021. All patients had histologically proven IPMN. We used transfer learning to fine-tune a convolutional neural network and to classify “low grade IPMN” from “high grade IPMN/invasive carcinoma.” Our test set consisted of 1823 images from 27 patients, recruiting 11 patients retrospectively, 7 patients prospectively, and 9 patients externally. We compared our results with the prediction based on international consensus guidelines.Results Our approach could classify low grade from high grade/invasive carcinoma in the test set with an accuracy of 99.6 % (95 %CI 99.5 %–99.9 %). Our deep learning model achieved superior accuracy in prediction of the histological outcome compared with any individual guideline, which have accuracies between 51.8 % (95 %CI 31.9 %–71.3 %) and 70.4 % (95 %CI 49.8–86.2).Conclusion This pilot study demonstrated that deep learning in IPMN-EUS images can predict the histological outcome with high accuracy.